PREFERENSI KONSUMEN TERHADAP FAKTOR-FAKTOR PENENTU KEPUASAN KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN PERUMAHAN BERSUBSIDI DI KARAWANG - Anthony, Budi; Tresani, Nurahma; Halim, Ricky Pittra (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2017)
In the conditions of competitions among subsidized housing developers, attention should be given to the determinants of consumer satisfactions in the purchasing process of subsidized housing products, especially in Karawang. The low price of land in Karawang is expected to stimulate developers to build subsidized housing. Million House Program from Kemenpera provides a very low 5% price subsidy and a constant interest rate over the tenor of credit. However, this does not automatically make consumers buy subsidized houses built in Karawang. Therefore, the authors conduct research by distributing questionnaires directly to residents in Taman Palumbon Asri housing. Bhumi Baru Indah Persada and Griya Indah which is all located in Karawang. The purpose of this research is to identify the influence of price factor, location, condition of environment and condition of building to decision making of purchase and to identify consumer satisfaction toward subsidized housing, with sample 3 subsidized housing in Karawang. Whiter uses Index Compatibility Level to measure level of satisfaction and level of interest for each housing, and then analyze them by considering each factors (location, price, quality of building, and environmental factors)Keywords: Price, Location, Building, Environment, Consumer Satisfaction, Purchasing Decision, Index Compatibility Level.